The War we Could not Stop : The Real Story of the Battle for Iraq - Edited by Randeep Ramesh (London Faber and Faber, 2003)
It took three weeks for the second Gulf War to shake the world, despite public protest and international negotiation. Here, Guardian journalists - some of them in the heat of battle, some of them at a more reflective distance around the world - tell the story of this controversial war.
Keywords: Iraq War (2003-2011) -- Iraq